Efektivitas Konsumsi Jus Alpukat Dan Bayam Terhadap Pasien Dengan Kadar Kolesterol Tinggi - Ari Khusuma; Annisa Agata; Arini Pradita Roselyin (Poltekkes Kemenkes Mataram, 2020)
Background: High cholesterol levels can cause various diseases such as atherosclerosis, coronary heart risk, heart attack, and angina. Based on a report on Rajabasa Indah Public Health Center there are 43 people with high cholesterol, one of the traditional medicine that can help lower cholesterol is avocado and spinach juice. The objective of this research was to the effect of consuming avocadoand spinach juice on blood cholesterol levels at Rajabasa Indah the Working Area of Public Health Center Lampung Province District. Objectives : The objective of this research was to the effect of consuming avocadoand spinach juice on blood cholesterol levels at Rajabasa Indah the Working Area of Public Health Center Lampung Province District. Methods : The type of quantitative research with experiment one group pre-test post-test design. The population was 43 people with hypertension, stroke, and heart who have high cholesterol levels in Rajabasa Indah of Public Health Center Lampung Province. 43 respondent samples were taken with accidental sampling. Data were analyzed with bivariate analysis with T Dependent (paired sample) test with 95% CI and α = 0.05. Results : The results showed that average value 298,77 cholesterol levels before consuming spinach and avocado juice and average value 280,09 cholesterol levels after consuming juice. Bivariate analysis result with α=0.05 showed that is an effect consuming avocado and spinach juice on to blood cholesterol levels (p< α 0,05). The researcher suggests to health workers to improve health education aimed at the community about risk of high cholesterol.